Early Photography in the Rijksmuseum’s Collection: A Group of Glass Negatives from the Estate of Laurens Lodewijk Kleijn (1826-1909) - M'rani Alaoui, Malika (The Rijksmuseum Bulletin, 2020)
In 1999 a group of nineteenth-century glass negatives were transferred to the Rijksmuseum from the University of Leiden’s Print Room. The negatives came from the estate of the Dutch artist Laurens Lodewijk Kleijn (1826-1909), who also made them. Kleijn lived in Rome between 1851 and 1868, became interested in photography and began to experiment with the medium. While he was in Italy, he came into contact with Princess Marianne, who awarded him a number of commissions. He also looked after her sizeable collection, first in Rome, later in her museum in Erbach. As the curator, Kleijn photographed part of the collection and the museum’s interior. These photographs were used for a museum catalogue and for picture postcards. The Rijksmuseum’s glass negatives show a variety of artworks from the princess’s collection. There are more experimental shots, too, family photographs and portraits, and photographs of paintings by Kleijn and of his studio. Thanks to the surviving glass negatives – and the artist’s estate as a whole – it was possible to reconstruct his interesting life story and take a fresh look at the history of photography.